Kinematics of the lumbar muscles in rowing: a preliminary study - Retailleau, M.; Domalain, M.; Ménard, M.; Colloud, F. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Rowing is a very physical activity requiring full range of joint motion associate with the generation of large forces at the feet and hands. The low back joints act to transfer these forces between the upper and lower extremities. As a result, low back injuries are the most common injuries observed in rowing, comprising 25-45% of the reported injuries requiring a medical attention (Teitz et al. 2001).